Implementasi Kebijakan Dalam Pengelolaan Sampah Di Kabupaten Sampang - Rizal Rohdianto; Rachmawati Novaria; Adi Soesiantoro (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research examines the implementation of waste management policies in Sampang Regency using Edward III's policy implementation theory. The research method used is descriptive qualitative with data collection through observation, interviews and documentation. The research results show that the implementation of waste management policies in Sampang Regency has not been optimal. Analysis based on Edward III's four indicators which reveal Communication, Resources, Bureaucratic Structure and Disposition. This research hopes to increase facility assistance, human resource training and coordination between parties to optimize waste management in Sampang Regency.